Efficient synthesis of the sponge alkaloids cyclostellettamines A-F - Baldwin, J; Spring, DR; Atkinson, C; Lee, V (1998)
The total synthesis of cyclostellettamines A-F is reported. The synthetic cyclostellettamines were reduced to the neutral bis- tetrahydropyridine compounds, and exact mass measurements of these reduced products provided unequivocal evidence for the cyclostellettamine structures.